Maternidade: sim ou não? Por quê? - Abranches, Maria Regina Josua (1990)
This dissertation aimed to identify the factors that conduct the women of today to decide for or against motherhood, as well as to identify her feelings about the subject. An exploratory field research was conducted using the life-history technique. Thirty one middle class working women, with no children, and in hers thirties, were Interviewed and offered statements about their decisions on procreate or note from the analysis of the statements we found that the degree of anxiety to make a choice seems to vary according to the extension of inner conflicts. These conflicts seems to derive from two sources: a) the degree of Interior disposability to become a mother; b) the degree of support from external sources. Emotional questions were clearly the more Influential actor to come to a resolution on the matter. The woman of today, although more acting socially. seems to fear that eventual renunciation to the maternal status may, In the future be sensed as a vacuum. This study made manifest that In the long run - with the Increment of the inner psychological pressure to make a decision -the women tend to be well-inclined toward motherhood.